(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article examines religious values in the Kyrgyz Republic as an important component of spiritual culture and social identity. It analyzes the historical foundations of religious beliefs among the Kyrgyz people, the characteristics of Islam as the dominant religion, and the influence of traditional beliefs and customs. Particular attention is given to the transformation of religious values in the post-Soviet period and their role in contemporary social development, social cohesion, and youth education. The study employs historical-cultural and comparative research methods.